2010
DOI: 10.1093/toxsci/kfq189
|View full text |Cite
|
Sign up to set email alerts
|

Primary Endothelial Damage Is the Mechanism of Cardiotoxicity of Tubulin-Binding Drugs

Abstract: The use of tubulin binders (TBs) in the treatment of cancer often is associated with cardiotoxicity, the mechanism of which has not been elucidated. To test the hypothesis that interstitial cells of the myocardium are the primary target of TBs, we evaluated the acute effects of a single iv administration of three reference TBs: colchicine (0.2 and 2 mg/kg), vinblastine (0.5 and 3 mg/kg), and vincristine (0.1 and 1 mg/kg) 6 and 24 h after dosing. Mitotic arrest was identified at 24 h in all high-dose groups bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 19 publications
3
47
0
Order By: Relevance
“…2,6,7 A study by Mikaelian and colleagues 8 showed that tubulin-binding drugs (including vincristine and vinblastine) can induce cell-cycle arrest of the rapidly proliferating cardiac endothelial cells and cause myocardial infarction. Vincristine is more often reported to cause ischemic syndromes than is rituximab, but a catastrophic synergism of vincristine and rituximab certainly cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,7 A study by Mikaelian and colleagues 8 showed that tubulin-binding drugs (including vincristine and vinblastine) can induce cell-cycle arrest of the rapidly proliferating cardiac endothelial cells and cause myocardial infarction. Vincristine is more often reported to cause ischemic syndromes than is rituximab, but a catastrophic synergism of vincristine and rituximab certainly cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in the literature that vinca alkaloids, such as vincristine, cause endothelial damage and myocardial ischemia. [6,7] It has also been demonstrated that cardiotoxic effects of doxorubicin are associated with excessive free radical formation and decrease in antioxidant radicals, sarkolemmal sodium-calcium exchange deterioration, and disruption of energy metabolism in myocardial cells. [2,8] Doxorubicin has been responsible for cardiomyopathy, especially dilated cardiomyopathy, and its cardiotoxic affects are attenuated by vincristine.…”
Section: Discussionmentioning
confidence: 99%
“…Other classical chemotherapeutics, including cyclophosphamide (a nitrogen mustard inducing DNA alkylation [79]), bleomycin (antitumor antibiotic that induces DNA degradation) and vinca alkaloids (depolarizing agents causing spiral-like distortions of the cellular microtubules [80]) have been considered responsible for the endothelial damage.…”
Section: Vascular Damage Caused By Chemotherapymentioning
confidence: 99%